Breast myofibroblastoma in a woman: a case report - Reis, Rafaela Rabello; Leitzke, Cristiane Barma; Ciaccio, Victor Quarentei; Torquato, Letícia Enedina do Nascimento; Bettiol, Caroline Silva; Fernandes, Sofia Rubin (Mastology, 2024)
Breast myofibroblastoma is a rare benign neoplasm of mesenchymal origin with fibroblastic and myofibroblastic characterizations. Myofibroblastoma has a higher incidence in men between the ages of 50 and 70 years and is less common in women. It is described as a solitary, unilateral, painless and mobile tumor, with a firm consistency and slow growth. Microscopically, it is a non-encapsulated tumor, with lobular growth, consisting of spindle cells organized in short, intersecting fascicles and interrupted by bundles of hyalinized collagen. On ultrasound, it can manifest as a hypoechoic solid mass, well circumscribed, homogeneous and similar to fibroadenoma; whereas, on mammography, a single, well-defined, rounded or discretely lobulated lesion can be observed, without calcifications. We report here the case of a 58-year-old patient with no previous breast complaints, who presented with changes in ultrasound and mammography examinations performed for breast cancer screening. The examinations revealed a suspicious lump in the left breast, classified as BIRADS 4C. Core biopsy described a low-grade spindle cell neoplasm, showing no signs of invasion, with immunohistochemistry results suggesting myofibroblastoma. As treatment, a sectorectomy was performed, and the reevaluated material confirmed the diagnosis of myofibroblastoma due to the positive expression of the markers calponin, CD34, BCL2 and CD99.